Answer:
[tex](x+2)^2 + (y-3)^2 = 10[/tex]
Step-by-step explanation:
The standard equation for circle is
[tex](x-a)^2 + (y-b)^2 = r^2[/tex]
where point (a,b) is coordinate of center of circle and r is the radius.
______________________________________________________
Given
center of circle =((-2,3)
let r be the radius of circle
Plugging in this value of center in standard equation for circle given above we have
[tex](x-a)^2 + (y-b)^2 = r^2 \ substitute (a,b) \ with (-2,3) \\=>(x-(-2))^2 + (y-3)^2 = r^2 \\=>(x+2)^2 + (y-3)^2 = r^2 (1)[/tex]
Given that point (1,2 ) passes through circle. Hence this point will satisfy the above equation of circle.
Plugging in the point (1,2 ) in equation 1 we have
[tex]\\=>(x+2)^2 + (y-3)^2 = r^2 \\=> (1+2)^2 + (2-3)^2 = r^2\\=> 3^2 + (-1)^2 = r^2\\=> 9 + 1 = r^2\\=> 10 = r^2\\=> r^2 = 10\\[/tex]
now we have value of r^2 = 10, substituting this in equation 1 we have
Thus complete equation of circle is [tex]=>(x+2)^2 + (y-3)^2 = r^2\\=>(x+2)^2 + (y-3)^2 = 10[/tex]